Sulianti Saroso's Thoughts on Maternal Reproductive Health in Indonesia 1950”1961 - Aini, Syarifah; Amini, Mutiah (Universitas Airlangga, 2023)
This research aims to discuss Sulianti Saroso as one of the important figures in the development of maternal reproductive health in Indonesia. Specifically, this research is focused on the period 1950-1961 based on Sulianti Saroso's many ideas related to maternal reproductive health which she pioneered while serving as Head of the Maternal and Child Welfare in Indonesia during that period. To understand her thoughts, the author used several primary sources in the form of ego documents including the memoirs of Sulianti Saroso's first child, the archives of Sulianti's biography that she wrote herself, as well as the archives of Sulaiman's biography. To support this research, the author also used her interviews's archives from Kedaulatan Rakyat Newspaper as well as some newspapers from the National Library of Indonesia, Solo Press Museum, and Dhelper. Meanwhile, for data analysis, the author used five stages of historical research, namely topic selection, source collection, verification, interpretation, and historiography. The results of the analysis then highlighted that as a figure who represents intellectual women, Sulianti's thoughts have a major contribution relevant to the development of maternal reproductive health in Indonesia. In conclusion, Sulianti Saroso can be considered as a significant figure in Indonesian health development.